2005
DOI: 10.1177/000348940511400608
|View full text |Cite
|
Sign up to set email alerts
|

Use of Interferon-Alpha in Recurrent Respiratory Papillomatosis: 20-Year Follow-up

Abstract: The obtained results revealed maximal effectiveness of IFN-alpha therapy in RRP patients with HPV 6 as compared with HPV 11. The association of HPV 11 with a worse long-term response to IFN-alpha therapy and a higher incidence of malignant transformation and mortality is clinically important and indicates the necessity of HPV typing in RRP patients after the first biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
62
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 30 publications
1
62
0
7
Order By: Relevance
“…It will therefore be interesting to assess whether the events that we have reported here are also seen in patients, based on analysis of IRF-1 expression and function during both active viral replication and selection of integrants. This could in part explain the various clinical outcomes of IFN therapy of papillomatoses and the differential regulation of HPV expression observed in various cancer cell lines upon IFN treatment (9,19). Similarly, studies on the effect of E5 protein on IFN expression in the natural context of the complete viral genome during a de novo HPV infection would help to further elucidate its normal functions, as already reported for E5 activity on cell proliferation (40).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It will therefore be interesting to assess whether the events that we have reported here are also seen in patients, based on analysis of IRF-1 expression and function during both active viral replication and selection of integrants. This could in part explain the various clinical outcomes of IFN therapy of papillomatoses and the differential regulation of HPV expression observed in various cancer cell lines upon IFN treatment (9,19). Similarly, studies on the effect of E5 protein on IFN expression in the natural context of the complete viral genome during a de novo HPV infection would help to further elucidate its normal functions, as already reported for E5 activity on cell proliferation (40).…”
Section: Discussionmentioning
confidence: 71%
“…There has been sustained interest in using IFNs and other immunomodulators to treat benign and premalignant HPVassociated lesions; however, inconsistent clinical outcomes have been observed (19,24), and the mechanistic bases for these inconsistencies are not yet understood.…”
Section: Discussionmentioning
confidence: 99%
“…Interferons (IFNs) have a critical role in the generation of an innate immune response against invading pathogens and, as a consequence, are an approved therapy for many diseases 1,2 including human papillomavirus (HPV)-associated diseases. 3,4 On infection, IFNs are synthesized and secreted to evoke anti-viral, 5 anti-tumor, 6 and immunoregulatory (reviewed in Stetson and Medzhitov 7 ) activity conferring protection to neighboring cells. Two main classes of IFNs exist.…”
mentioning
confidence: 99%
“…However, debate is ongoing regarding the effectiveness of long-term IFN-α therapy, with even multicenter studies on the application of IFN-α as an adjuvant for RRP therapy providing contradictory results 13,15 . A recent study revealed the maximal effectiveness of INF-α therapy in patients having RRP with HPV 6 as compared to HPV 11 12 . In addition, these results suggest that long-term IFN-α therapy (mean 32.4±21.6 months) 12 was more effective in preventing relapse than the a short course (0.5 or 1 year) 13,15 of injection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed the maximal effectiveness of INF-α therapy in patients having RRP with HPV 6 as compared to HPV 11 12 . In addition, these results suggest that long-term IFN-α therapy (mean 32.4±21.6 months) 12 was more effective in preventing relapse than the a short course (0.5 or 1 year) 13,15 of injection. Accumulation of additional evidence, however, is required to determine the dosage and duration of IFN-α treatment suitable for patients with RRP.…”
Section: Discussionmentioning
confidence: 99%